2017
DOI: 10.1021/acs.jafc.6b04716
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Characterization of Potentially Prebiotic Oligosaccharides in Brewed Coffee and Spent Coffee Grounds

Abstract: Oligosaccharides are indigestible carbohydrates widely present in mammalian milk and in some plants. Milk oligosaccharides are associated with positive health outcomes; however, oligosaccharides in coffee have not been extensively studied. We investigated the oligosaccharides and their monomeric composition in dark roasted coffee beans, brewed coffee, and spent coffee grounds. Oligosaccharides with a degree of polymerization ranging from 3 to 15, and their constituent monosaccharides, were characterized and qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
29
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(32 citation statements)
references
References 44 publications
1
29
0
Order By: Relevance
“…In 2019, the world s coffee production is forecast to reach a peak value of 174.5 million bags of 60 kg, much higher than previous years, according to the statistics of the U.S. Department of Agriculture [5,6]. Owing to its considerable demand, the resulting waste of coffee grinds could be substantial [7]. Apart from being a rich source of caffeine, it includes several different chemicals such as vitamins, carbohydrates, lipids, minerals, alkaloids, phenolic, and nitrogen-rich compounds [4].…”
Section: Introductionmentioning
confidence: 99%
“…In 2019, the world s coffee production is forecast to reach a peak value of 174.5 million bags of 60 kg, much higher than previous years, according to the statistics of the U.S. Department of Agriculture [5,6]. Owing to its considerable demand, the resulting waste of coffee grinds could be substantial [7]. Apart from being a rich source of caffeine, it includes several different chemicals such as vitamins, carbohydrates, lipids, minerals, alkaloids, phenolic, and nitrogen-rich compounds [4].…”
Section: Introductionmentioning
confidence: 99%
“…In our previous study, a series of oligosaccharides DP 3-15 were separated from A. lancea and identified as FOS, which consisting of linear ÎČ-(2,1)-linked fructofuranosyl units mostly carry a terminal single α-(1–2)-linked α-glucopyranosyl unit [10–12]. It is a well-recognized class of prebiotics [13–15], which are dietary ingredients that cannot be digested by human-produced digestive enzymes, yet they provide a health benefit to the host mediated by selectively stimulating the growth and/or activity of one or a limited number of host gut microbiota [16]. It is becoming increasingly clear that FOS can reduce or prevent gastroenteritis, inflammatory bowel disease (IBS), reduce the risk of colon cancer and reduce potentially pathogenic gastro-intestinal bacteria [17].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have characterized how aroma compounds are extracted relating to polarity and volatility, and have demonstrated that more polar (and therefore more water‐soluble) compounds are extracted early . Furthermore, sweetness is a desirable sensory property for coffee consumers, and coffee is known to have sucrose, oligosaccharides, and polysaccharides in green, roasted, and brewed coffee in varying quantities …”
Section: Introductionmentioning
confidence: 99%